Limestone powder for steelmaking and preparation method and application thereof
Through pretreatment, surface modification, mechanical activation and composite preparation steps, a kind of limestone powder for steelmaking was prepared, which solved the problems of purity, particle size, reaction efficiency, thermal stability and storage transportation of traditional limestone powder during steelmaking, significantly improved the reaction activity, fluidity and storage stability, and improved the steelmaking efficiency and steel quality.
Patent Information
- Application Number
- CN202411543305.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Traditional limestone powder has problems such as low purity, uneven particle size, low reaction efficiency, poor thermal stability and difficult storage and transportation during steelmaking, which affects the quality of steel and production costs.
A kind of limestone powder for steelmaking was prepared through pretreatment, surface modification, mechanical activation and composite preparation steps. Pretreatment includes the selection of high-purity limestone, crushing, sorting, cleaning and drying. Surface modification improves reactive activity and fluidity through nanomaterial coatings. Mechanically activated the particles are refined by ball milling and fine powders of suitable particle size are obtained by grading. Composite material preparation is mixed with dolomite powder, fluorite powder, magnesium sand, silica fume and iron ore powder and calcined to form a stable composite structure.
It significantly improves the reactivity, fluidity, thermal stability and storage stability of limestone powder, improves the desulfurization efficiency during steelmaking and the alkalinity and fluidity control effect of the furnace slag, and reduces the production cost and difficulty in storage and transportation.
Smart Images

Figure BDA0005113249660000111 
Figure BDA0005113249660000121 
Figure BDA0005113249660000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of limestone powder preparation, and in particular relates to limestone powder for steelmaking and a preparation method and application thereof. Background Art
[0002] The steel industry is one of the important basic industries of the national economy. With the acceleration of the global industrialization process, the demand for high-quality steel is increasing. In the modern steelmaking process, limestone powder, as an important auxiliary material, plays a key role in desulfurization and slag making. However, traditional limestone powder has many problems in use, such as low purity, uneven particle size, low reaction efficiency, etc. These problems directly affect the quality and production cost of steel.
[0003] The main component of limestone powder is calcium carbonate (CaCO3), which decomposes at high temperatures to form calcium oxide (CaO) and carbon dioxide (CO2). The main functions of CaO in the steelmaking process include: (1) Desulfurization: CaO can react with sulfides in molten steel to form easily removable calcium sulfide (CaS), thereby reducing the sulfur content in steel and improving the mechanical properties of steel. (2) Slag formation: CaO participates in the formation of slag and controls the metallurgical process by adjusting the basicity of the slag. At the same time, the slag also plays a role in protecting the furnace lining. (3) Adjusting the molten pool temperature: The right amount of CaO helps to improve the heat distribution in the molten pool and promotes uniform heating and mixing of the metal.
[0004] Although limestone powder plays an important role in steelmaking, it still faces the following challenges in practical applications: (1) Insufficient purity: Natural limestone ore contains a certain proportion of impurities, such as silicon dioxide (SiO2) and magnesium oxide (MgO), which can affect the properties of the slag and even cause adverse reactions. (2) Uneven particle size: Particles of different sizes can affect the reaction rate and slag fluidity. Particles that are too coarse react slowly, while particles that are too fine tend to fly around, causing dust pollution. (3) Poor thermal stability: Some limestone powder tends to agglomerate under high temperature conditions, affecting its dispersibility and reactivity in the molten pool. (4) Difficulty in storage and transportation: Because limestone powder has strong hygroscopicity and is easy to agglomerate, it brings inconvenience to storage and transportation, and may cause blockage in the conveying system.
[0005] In order to solve the above problems, researchers and engineers have been exploring ways to improve limestone powder. For example, limestone powder can be modified by physical or chemical methods to improve its reactivity and performance. Modified limestone powder usually has finer particle size, higher purity and more stable quality, thus showing better desulfurization and slag-making effects in the steelmaking process.
[0006] The preparation methods of modified limestone powder in the prior art mainly include mechanical activation, chemical modification and heat treatment. The mechanical activation method refines the particle size of limestone powder by means of high-energy ball milling, thereby improving its reactivity. The chemical modification method improves the dispersibility and reactivity of limestone powder by adding certain chemical substances, such as surfactants and dispersants. The heat treatment method changes the crystal structure of limestone powder by high-temperature calcination, thereby improving its activity.
[0007] Although the above methods have improved the performance of limestone powder to a certain extent, there are still some problems. For example, although the mechanical activation method can refine the particle size, it has high energy consumption and causes great wear on the equipment. Although the chemical modification method can improve the dispersibility, the introduced chemical substances may cause environmental pollution. Although the heat treatment method can improve the crystal structure, the high-temperature calcination process also consumes high energy and has strict requirements on the equipment.
[0008] Therefore, developing a new limestone powder for steelmaking and a preparation method thereof to solve the above problems is of great significance for the sustainable development of the steel industry. Summary of the invention
[0009] The purpose of the present invention is to provide limestone powder for steelmaking and a preparation method and application thereof. The present invention improves the reaction activity of the limestone powder, improves the fluidity and reaction uniformity of the particles, and enhances the storage stability of the limestone powder.
[0010] In order to achieve the above object, the present invention provides the following technical solutions:
[0011] A method for preparing limestone powder for steelmaking comprises the following steps:
[0012] 1. Preprocessing stage
[0013] Raw material selection: natural limestone with CaCO3 content greater than 95% is selected as raw material;
[0014] Crushing and sorting: The limestone raw materials are crushed to a particle size of less than 10 mm, and the crushed materials are separated by gravity to remove impurities;
[0015] Cleaning and drying: Use a high-pressure water gun to clean the limestone, and then put the cleaned limestone into a drying furnace for drying;
[0016] 2. Surface modification stage
[0017] Mixing nano silicate, nano aluminum oxide, nano zinc oxide, nano lanthanum oxide and nano yttrium oxide, adding the mixture into water containing a dispersant to prepare a suspension, controlling the pH value of the suspension to be 7-10, adding dried limestone into the suspension, stirring, and spray drying the mixture to obtain surface-modified limestone;
[0018] 3. Mechanical activation stage
[0019] Ball milling: The surface-modified limestone is fed into a high-energy ball mill for grinding;
[0020] Classification: Use an air classifier to classify the ball-milled powder and separate fine powder with a particle size of 5-10 μm;
[0021] 4. Composite material preparation stage
[0022] Additive mixing: Mix the mechanically activated limestone powder with dolomite powder, fluorite powder, magnesia, silica fume and iron ore powder;
[0023] Calcination: Calcinate the mixed materials and cool them to room temperature to obtain a composite material, namely the limestone powder for steelmaking.
[0024] In a preferred embodiment, the drying temperature in the pretreatment stage is controlled at 100-120° C., and the drying time is 3-5 hours.
[0025] In a preferred embodiment, the nano-silicate is one or more of nano-zinc silicate, nano-magnesium silicate, nano-aluminum silicate, and nano-calcium silicate.
[0026] In a preferred embodiment, the mass ratio of nano-silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide and nano-yttrium oxide is 3-5:3-5:1-2:0.05-0.1:0.1-0.5.
[0027] In a preferred embodiment, the mass ratio of the total mass of nano-silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide and nano-yttrium oxide to the mass ratio of limestone in the surface modification stage is 1 to 2:10.
[0028] In a preferred embodiment, the dispersant in the surface modification stage is a mixture of sodium lauryl sulfate, fatty alcohol polyoxyethylene ether, and polyvinyl alcohol in a mass ratio of 3-5:1:0.3-0.8, and the amount of the dispersant is 0.5-3% of the total solid mass.
[0029] In a preferred embodiment, the solid content in the suspension is 10-20 wt %.
[0030] In a preferred embodiment, the stirring speed in the surface modification stage is 200-800 rpm, and the stirring time is 30-60 minutes, until the suspension is stable and there is no obvious agglomeration phenomenon.
[0031] In a preferred embodiment, the air inlet temperature of the spray drying is controlled at 200-250° C., and the air outlet temperature is controlled at 80-100° C., so that a uniform coating is formed on the surface of the limestone.
[0032] The surface modification step of the present invention significantly improves the reaction activity, fluidity, thermal stability and storage stability of the product by forming a uniform nanomaterial coating on the surface of the limestone powder. By forming a uniform nanomaterial coating on the surface of the limestone, its specific surface area can be increased, thereby increasing the reaction rate with the sulfide in the molten steel, while helping to reduce the agglomeration between particles, so that the limestone powder is more evenly distributed in the molten pool, and improving the desulfurization efficiency. The nanomaterial coating can also make the particle surface smoother, reduce the friction between particles, and prevent the particles from absorbing moisture and agglomerating in a humid environment, thereby improving fluidity and operability. The use of nanomaterials can also change the crystal structure of the limestone powder, making it more stable at high temperatures. The selection and proportion of nanomaterials will affect the uniformity and density of the coating, and then affect the performance of the product. There is a synergistic effect between different nanomaterials, and a reasonable proportion can make the advantages of these materials complement each other, thereby improving the overall performance. The addition of nano lanthanum oxide and nano yttrium oxide can significantly improve the desulfurization efficiency, but if the proportion is not appropriate, the expected effect cannot be achieved.
[0033] The selection and proportion of the dispersant in the method of the present invention directly affect the dispersion effect of the nano material in the suspension. Suitable dispersants can ensure that the nano material is evenly distributed in the suspension to form a stable suspension system, thereby providing a uniform and dense coating. In addition, suitable dispersant combinations can reduce the friction between particles and improve the fluidity and operability of the product.
[0034] In a preferred embodiment, the rotation speed of the ball mill in the mechanical activation stage is 200-300 rpm, the grinding time is 2-6 hours, the ball milling medium is a steel ball or a ceramic ball with a diameter of 5-10 mm, and the filling rate is 40-50%.
[0035] The present invention optimizes parameters such as the rotation speed, time, medium and filling rate of the ball milling process in the ball milling process, so that a dynamic balance can be achieved between particle refinement and coating wear, and the coating can still maintain a certain integrity and uniformity while refining the particles.
[0036] In addition, the present invention chooses to perform surface modification first and then mechanical activation, which can reduce the introduction of impurities during the ball milling process and maintain a high purity. Although part of the coating will be destroyed during the ball milling process, some particles still retain the coating and can meet the performance requirements of the final product.
[0037] In a preferred embodiment, the mass percentage of each component in the composite material preparation stage is: limestone powder 80-85%, dolomite powder 5-10%, fluorite powder 3-7%, magnesia 2-3%, silica fume 1-2%, and iron ore powder 1-2%.
[0038] In a preferred embodiment, during the composite material preparation stage, the calcination temperature is 700-800° C., and the calcination time is 2-5 hours, preferably 3-4 hours.
[0039] The composite material preparation step of the present invention significantly improves the reaction activity, fluidity, thermal stability and storage stability of the product by mixing the mechanically activated limestone powder with a variety of additives and calcining. Specific additives can synergize with limestone powder to improve its desulfurization and slag-making efficiency in the steelmaking process, adjust the basicity and fluidity of the slag, and thus improve the control effect in the metallurgical process. The addition of additives can make the particle distribution more uniform, reduce agglomeration, reduce the friction between particles, and improve the overall fluidity. The additives can form a stable composite structure with the limestone powder and improve its thermal stability at high temperatures. The additives can also improve the anti-hygroscopicity of the product and reduce agglomeration and deterioration during storage. Appropriate calcination temperature and time in the calcination stage can ensure that various components fully react to form a stable composite structure. Too high a temperature may cause particle agglomeration and agglomeration and decomposition of calcium carbonate, and too long a time may cause excessive sintering of the material, affecting fluidity.
[0040] The present invention also provides limestone powder prepared by the method and application of the limestone powder in a steelmaking process.
[0041] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0042] The limestone powder for steelmaking and the preparation method thereof provided by the present invention significantly improve the reactivity, fluidity, thermal stability and storage stability of the limestone powder. By introducing nanomaterials for surface modification, the specific surface area is increased, and the reaction rate in the desulfurization process is promoted; at the same time, the agglomeration phenomenon between particles is reduced, ensuring that the limestone powder is more evenly distributed in the molten pool, thereby improving the desulfurization efficiency. In addition, the application of specific additives not only optimizes the basicity and fluidity of the slag, but also enhances the anti-hygroscopicity of the product and reduces the agglomeration problem that may occur during storage. The entire process flow is reasonably designed, which effectively solves the problems of poor reactivity, poor fluidity, and difficulty in storage of traditional limestone powder, and is of great significance to the sustainable development of the steel industry. DETAILED DESCRIPTION
[0043] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.
[0044] The following sources of raw materials are provided for illustrative purposes:
[0045] Nano-calcium silicate was purchased from Shanghai National Engineering Research Center for Nanotechnology and Application Co., Ltd., with an average particle size of 50-100 nm;
[0046] Nano-alumina was purchased from Shandong Luyang Energy Saving Materials Co., Ltd., with an average particle size of 30-50 nm;
[0047] Nano zinc oxide was purchased from Guangzhou Jibisheng Technology Industry Co., Ltd., with an average particle size of 30-80 nm;
[0048] Nano-lanthanum oxide was purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd., with an average particle size of 30-50 nm;
[0049] Nano-yttrium oxide was purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd., with an average particle size of 30-50 nm;
[0050] Dolomite powder was purchased from Fengrun District Mining Company, Tangshan City, Hebei Province, 400 mesh, CaCO3 content ≥95%;
[0051] Fluorite powder was purchased from Hunan Xiangtan Electrochemical Technology Co., Ltd., 200 mesh, CaF2 content ≥ 97%;
[0052] Magnesia was purchased from Liaoning Yingkou Qinghua Refractory Material Co., Ltd., 100 mesh;
[0053] Silica fume was purchased from Beijing Zhongjian Special Cement Co., Ltd., with a specific surface area of 15000-20000m2 / kg;
[0054] Iron ore powder was purchased from Anshan Iron and Steel Group Mining Co., Ltd., 100 mesh, Fe content ≥ 62%.
[0055] Example 1
[0056] This embodiment provides a method for preparing limestone powder for steelmaking, comprising the following steps:
[0057] 1. Preprocessing stage
[0058] Raw material selection: natural limestone with a CaCO3 content of 98.2% is used as raw material;
[0059] Crushing and sorting: The limestone raw materials are crushed to a particle size of less than 10 mm, and the crushed materials are separated by gravity to remove impurities;
[0060] Cleaning and drying: Use a high-pressure water gun to clean the limestone, and then put the cleaned limestone into a drying furnace and dry it at 110°C for 4 hours;
[0061] 2. Surface modification stage
[0062] Nano calcium silicate, nano aluminum oxide, nano zinc oxide, nano lanthanum oxide and nano yttrium oxide are mixed in a mass ratio of 5:3:2:0.08:0.2 to obtain a mixture, the mixture is added into water containing a dispersant (a mixture of sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and polyvinyl alcohol in a mass ratio of 4:1:0.5) to prepare a suspension, the solid (mixture and dispersant) content in the suspension is made to be 16wt%, the pH value of the suspension is adjusted to 8, dried limestone is added to the suspension, stirred at a speed of 500rpm for 50 minutes, and after stirring, the mixture is spray-dried, the air inlet temperature is controlled at 230°C, and the air outlet temperature is controlled at 90°C to obtain surface-modified limestone;
[0063] The mass ratio of the total mass of nano calcium silicate, nano aluminum oxide, and nano zinc oxide to limestone is 2:10; the amount of sodium dodecyl sulfate used is 1% of the total mass of the solid;
[0064] 3. Mechanical activation stage
[0065] Ball milling treatment: The surface-modified limestone was fed into a high-energy ball mill for grinding. The speed of the ball mill was 240 rpm, the grinding time was 5 hours, the ball milling medium was a steel ball with a diameter of 8 mm and a filling rate of 40%;
[0066] Classification: Use an air classifier to classify the ball-milled powder and separate fine powder with a particle size of 5-10 μm;
[0067] 4. Composite material preparation stage
[0068] Additive mixing: Mix the activated limestone powder with additives according to the following mass percentages: limestone powder 83%, dolomite powder 8%, fluorite powder 4%, magnesia 2%, silica fume 1.5%, iron ore powder 1.5%;
[0069] Calcination: Calcine the mixed materials at 760°C for 3 hours and cool them to room temperature to obtain the limestone powder for steelmaking.
[0070] Example 2
[0071] This embodiment provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that the mass ratio of nano-calcium silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide, and nano-yttrium oxide is 4:4:2:0.1:0.3, and the mass ratio of the total mass of nano-calcium silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide, and nano-yttrium oxide to the mass ratio of limestone is 1:10.
[0072] Example 3
[0073] This embodiment provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that the mass percentages of limestone powder and additives are: limestone powder 80%, dolomite powder 8%, fluorite powder 6%, magnesia 2%, silica fume 2%, and iron ore powder 2%.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that only nano calcium silicate is used as the nano material in the surface modification stage.
[0076] Comparative Example 2
[0077] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that the mass ratio of nano-calcium silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide and nano-yttrium oxide in the surface modification stage is 5:1:2:0.08:0.05.
[0078] Comparative Example 3
[0079] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that nano-lanthanum oxide and nano-yttrium oxide are not contained in the surface modification stage.
[0080] Comparative Example 4
[0081] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that ordinary calcium silicate, aluminum oxide, zinc oxide, lanthanum oxide and yttrium oxide are used in the surface modification stage, and the particle sizes are respectively: calcium silicate 5-10μm, aluminum oxide 0.1-10μm, zinc oxide 0.1-10μm, lanthanum oxide 1-10μm, and yttrium oxide 1-10μm.
[0082] Comparative Example 5
[0083] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that the dispersant is a mixture of sodium lauryl sulfate, fatty alcohol polyoxyethylene ether, and polyvinyl alcohol in a mass ratio of 1:4:0.5.
[0084] Comparative Example 6
[0085] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that the dispersant is a mixture of sodium hexametaphosphate, polyvinyl alcohol and sodium polyacrylate in a mass ratio of 4:1:0.5.
[0086] Comparative Example 7
[0087] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that the mass percentages of limestone powder and additives are: limestone powder 80%, dolomite powder 12%, and fluorite powder 8%.
[0088] Comparative Example 8
[0089] This comparative example provides a method for preparing limestone powder for steelmaking, which differs from Example 1 in that nano calcium silicate is replaced by nano sodium silicate.
[0090] Comparative Example 9
[0091] This comparative example provides a method for preparing limestone powder for steelmaking, which is different from Example 1 in that in the composite material preparation stage, the activated limestone powder is mixed with additives according to the following mass percentages: 83% limestone powder, 5% glass fiber, 2% clay powder, and 10% carbonized wood waste powder.
[0092] Comparative Example 10
[0093] This comparative example provides a method for preparing limestone powder for steelmaking, which differs from Example 1 in that the calcination time in the composite material preparation stage is 6 hours.
[0094] Performance test 1: Desulfurization efficiency test
[0095] Prepare 1000 grams of sulfur-containing molten steel with an initial sulfur content of 100 ppm, weigh 10 grams of limestone powder to be tested (limestone powder prepared in Examples 1-3 and Comparative Examples 1-10). Heat the sulfur-containing molten steel to 1600° C. in a high-temperature furnace, add limestone powder, ensure that the limestone powder and the molten steel are fully mixed, react for 30 minutes, and after the reaction is completed, take out a certain amount of molten steel sample to measure the sulfur content in the molten steel.
[0096] The desulfurization efficiency is calculated according to the following formula:
[0097] Desulfurization efficiency (%) = ((initial sulfur content - sulfur content after reaction) / initial sulfur content) × 100%.
[0098] The test results are shown in Table 1.
[0099] Table 1 Desulfurization efficiency test results
[0100]
[0101]
[0102] The above results show that the limestone powder preparation method provided by the present invention can significantly improve the desulfurization efficiency of limestone powder. Comparative Example 1 uses a single nanomaterial and lacks the synergistic effect of other nanomaterials, resulting in a decrease in desulfurization efficiency. The proportion of nano-lanthanum oxide and nano-yttrium oxide in Comparative Example 2 is too low. Nano-lanthanum oxide and nano-yttrium oxide are important modified components. They can improve the reactivity and thermal stability of limestone powder. When these components are insufficient, the protective layer formed is not uniform enough, thereby reducing the desulfurization efficiency. The desulfurization efficiency of Comparative Example 3, which lacks these two components, is even lower. The micron-sized particles in Comparative Example 4 cannot provide sufficient specific surface area to enhance the reactivity, which results in the coating being not dense enough and the desulfurization performance of limestone powder cannot be effectively improved. The dispersant formula of Comparative Example 5 may not be able to effectively disperse the nanomaterial evenly in the suspension, resulting in uneven coating, thin or missing protective layers in some areas, thereby reducing the desulfurization efficiency. Comparative Example 6 replaces the dispersant combination, which is not suitable for this system, resulting in the nanomaterial not being well dispersed and attached to the limestone surface. In Comparative Example 7, the increase in the proportion of dolomite powder and fluorite powder affected the reactivity and fluidity of limestone powder, resulting in a decrease in desulfurization efficiency. In Comparative Example 8, the modification effect of nano-sodium silicate was not as good as that of nano-calcium silicate, resulting in a significant decrease in desulfurization efficiency. The additives in Comparative Example 9 may have caused agglomeration and adverse reactions, seriously affecting the desulfurization efficiency, proving that these additives are not suitable for limestone powder for steelmaking. In Comparative Example 10, the excessive calcination time may lead to a decrease in material properties, such as particle agglomeration or changes in crystal structure, thereby reducing the desulfurization efficiency.
[0103] Performance Test 2: Hygroscopicity Test
[0104] The limestone powder prepared in Examples 1-3 and Comparative Examples 1-10 was placed in a dryer and placed at room temperature for 24 hours to ensure that the samples were completely dry. 10 g of each sample was weighed and recorded as m0 as the sample to be tested. The sample was placed in a constant temperature and humidity chamber with pre-set conditions (temperature 25°C, relative humidity 85%) and exposed for 24 hours. The sample was taken out of the constant temperature and humidity chamber, quickly transferred to a dryer, and weighed after cooling to room temperature, and recorded as the mass after moisture absorption m1.
[0105] Calculate moisture absorption rate: Moisture absorption rate = ((m1-m0) / m0) × 100%
[0106] Each sample was tested three times and the average value was taken. The results are shown in Table 2.
[0107] Table 2 Hygroscopicity test results
[0108] Group <![CDATA[Initial mass m0 (g)]]> <![CDATA[Mass m1 (g) after moisture absorption]]> Moisture absorption rate (%) Example 1 10 10.050 0.50% Example 2 10 10.053 0.53% Example 3 10 10.051 0.51% Comparative Example 1 10 10.109 1.09% Comparative Example 2 10 10.115 1.15% Comparative Example 3 10 10.130 1.30% Comparative Example 4 10 10.145 1.45% Comparative Example 5 10 10.160 1.60% Comparative Example 6 10 10.175 1.75% Comparative Example 7 10 10.127 1.27% Comparative Example 8 10 10.151 1.51% Comparative Example 9 10 10.240 2.40% Comparative Example 10 10 10.254 2.54%
[0109] The above results show that the moisture absorption rates of Examples 1-3 are all lower than 1%, indicating that these samples have good stability in a humid environment, are not easy to absorb moisture, and are suitable for long-term storage and transportation. Comparative Example 1 uses a single nano calcium silicate for surface modification, lacks the synergistic effect of other nano materials, and cannot form a uniform and dense protective layer on the surface of limestone powder, resulting in increased hygroscopicity. Due to the imbalance of the proportion of nano materials in Comparative Example 2, a continuous and dense protective layer may not be formed on the surface of limestone powder, thereby increasing the possibility of moisture penetration. In Comparative Example 3, there is a lack of synergistic effect of nano yttrium oxide and nano lanthanum oxide, and the formed coating may have more pores and defects, making it easier to absorb moisture. The larger particles in Comparative Example 4 may cause the coating structure to be loose and the porosity to increase, making it easier for moisture to enter and be absorbed. The dispersant formulas of Comparative Examples 5 and 6 cannot effectively disperse the nano materials, resulting in uneven distribution of the nano materials in the suspension, which in turn affects the uniformity and density of the final coating, and there are local areas where the coating is thin or missing, which increases the hygroscopicity. The increase in the proportion of dolomite powder and fluorite powder in Comparative Example 7 may lead to an increase in the porosity of the mixture, making it easier for moisture to enter and be absorbed. The coating formed by the nano-sodium silicate in Comparative Example 8 may not be as stable and dense as that of the nano-calcium silicate, thereby reducing the anti-hygroscopic performance. The additives used in Comparative Example 9 may introduce more pores and voids, making it easier for moisture to penetrate and be absorbed, thereby significantly improving the hygroscopicity. The high-temperature calcination for too long in Comparative Example 10 may cause the particles of the material to agglomerate or the crystal structure to change, thereby reducing its specific surface area and porosity, and may also introduce some microcracks or defects, which will become channels for moisture absorption.
[0110] Performance Test 3: Fluidity Test
[0111] Fix the funnel at a height of 10 cm from the base, slowly pour the limestone powder into the funnel, let it flow out naturally and accumulate on the base to form a stable conical pile, measure the angle between the hypotenuse of the conical pile and the horizontal plane, which is the repose angle. Each sample was tested three times and the average value was taken. The results are shown in Table 3.
[0112] Table 3 Fluidity test results
[0113]
[0114]
[0115] The above results show that the repose angles of Examples 1-3 are low, indicating that these samples have good fluidity and are suitable for use in the steelmaking process. The use of a single nanomaterial in Comparative Example 1 may not form a uniform and dense protective layer on the surface of the limestone powder, resulting in increased friction between the particles and reduced fluidity. The high proportion of nano calcium silicate in Comparative Example 2 may promote the agglomeration of particles, forming larger clusters, affecting the flow properties of the powder. Comparative Example 3 lacks the synergistic effect of nano lanthanum oxide and nano yttrium oxide, and the formed coating may have more pores and defects, making the particles more likely to agglomerate, thereby affecting the fluidity. The micron-sized particles in Comparative Example 4 have a larger size than the nano-sized particles, which increases the contact area and friction between the particles, resulting in a decrease in fluidity. The poor effect of the dispersants in Comparative Examples 5 and 6 may cause the nanomaterials to not adhere well to the limestone surface, forming a discontinuous coating, increasing the agglomeration between the particles, and reducing the fluidity. The increase in the proportion of dolomite powder and fluorite powder in Comparative Example 7 may lead to an increase in the porosity in the mixture, thereby increasing the contact area between the particles, increasing the friction, and reducing the fluidity. The additives used in Comparative Example 8 may change the overall structure of the powder, making it more loose and irregular, further affecting the fluidity. The additives used in Comparative Example 9 are improper, and these additives may change the overall structure of the powder, making it more loose and irregular, further affecting the fluidity. The excessively long calcination time in Comparative Example 10 may destroy the structure of the material, causing particle agglomeration, further reducing the fluidity.
[0116] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing limestone powder for steelmaking, comprising the following steps: (1) Preprocessing stage Raw material selection: natural limestone with CaCO3 content greater than 95% is selected as raw material; Crushing and sorting: The limestone raw materials are crushed to a particle size of less than 10 mm, and the crushed materials are separated by gravity to remove impurities; Cleaning and drying: Use a high-pressure water gun to clean the limestone, and then put the cleaned limestone into a drying furnace for drying; (2) Surface modification stage Mixing nano-silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide and nano-yttrium oxide, adding the mixture into water containing a dispersant to prepare a suspension, controlling the pH value of the suspension to be 7-10, adding dried limestone into the suspension, stirring, and spray-drying the mixture to obtain surface-modified limestone, wherein the mass ratio of the nano-silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide and nano-yttrium oxide is 3-5:3-5:1-2:0.05-0.1:0.1-0.5, and the mass ratio of the total mass of the nano-silicate, nano-aluminum oxide, nano-zinc oxide, nano-lanthanum oxide and nano-yttrium oxide to the limestone is 1-2:10; (3) Mechanical activation stage Ball milling: The surface-modified limestone is fed into a high-energy ball mill for grinding; Classification: Use an air classifier to classify the ball-milled powder and separate fine powder with a particle size of 5-10 μm; (4) Composite material preparation stage Additive mixing: Mix the mechanically activated limestone powder with dolomite powder, fluorite powder, magnesia, silica fume and iron ore powder; Calcination: Calcinate the mixed materials and cool them to room temperature to obtain a composite material, namely the limestone powder for steelmaking.
2. The preparation method according to claim 1, characterized in that: The drying temperature in the pretreatment stage is controlled at 100-120°C, and the drying time is 3-5 hours.
3. The preparation method according to claim 1, characterized in that: The dispersant is a mixture of sodium lauryl sulfate, fatty alcohol polyoxyethylene ether and polyvinyl alcohol in a mass ratio of 3-5:1:0.3-0.8, and the amount of the dispersant is 0.5-3% of the total solid mass. The solid content in the suspension is 10-20wt%.
4. The preparation method according to claim 1, characterized in that: The stirring speed in the surface modification stage is 200-800 rpm, and the stirring time is 30-60 minutes; the air inlet temperature of the spray drying is controlled at 200-250°C, and the air outlet temperature is controlled at 80-100°C.
5. The preparation method according to claim 1, characterized in that: In the mechanical activation stage, the rotation speed of the ball mill is 200-300 rpm, the grinding time is 2-6 hours, the ball milling medium is a steel ball or ceramic ball with a diameter of 5-10 mm, and the filling rate is 40-50%.
6. The preparation method according to claim 1, characterized in that: The mass percentage of each component in the composite material preparation stage is: limestone powder 80-85%, dolomite powder 5-10%, fluorite powder 3-7%, magnesia 2-3%, silica fume 1-2%, and iron ore powder 1-2%.
7. The preparation method according to claim 1, characterized in that: In the composite material preparation stage, the calcination temperature is 700-800° C. and the calcination time is 2-5 hours.
8. The preparation method according to claim 7, characterized in that: During the composite material preparation stage, the calcination time is 3 to 4 hours.
9. limestone powder prepared by the method described in any one of claims 1 to 8.
10. Use of limestone powder prepared by the method according to any one of claims 1 to 8 in steelmaking process.
Citation Information
Patent Citations
Production process of active lime
CN108264247A
Precipitated calcium carbonate, a method for its manufacture and uses thereof
US20180244533A1